An agent model integrating an adaptive model for environmental dynamics. (16th May 2011) - Treur, Jan; Umair, Muhammad
The environments in which agents are used often may be described by dynamical models, e.g., in the form of a set of differential equations. In this paper, an agent model is proposed that can perform model-based reasoning about the environment, based on a numerical (dynamical system) model of the environment. Moreover, it does so in an adaptive manner by adjusting the parameter values in the environment model that represent believed environmental characteristics, thus, adapting these beliefs to the real characteristics of the environment.